The Relationship between Religion and Deviance in a Largely Irreligious Country: Findings from the 2010 China General Social Survey. Issue 10 (3rd October 2017) - Wang, Xiuhua; Jang, Sung Joon
ABSTRACT: We examined the religion–deviance relationship in China, analyzing the 2010 China General Social Survey data to estimate ordinary least squares, logistic, and negative binomial regression models. First, we found respondents who followed some form of religion to be no different from those without religion in law or rule violation. Second, respondents of folk religion were more favorable to unconventional sex than those without religion, and those of organized religion were less so. Finally, respondents of organized religion were less likely to report daily drinking and smoking than their irreligious counterparts, whereas those of folk religion were not different from the religious nones.